Polyethylenimine-based iron oxide nanoparticles enhance cisplatin toxicity in ovarian cancer cells in the presence of a static magnetic field - Ashoori, Faranak; Hajipour-Verdom, Behnam; Satari, Mohammad; Abdolmaleki, Parviz (Frontiers in Oncology, 2023)
Background Drug resistance in cancer cells is a major concern in chemotherapy. Cisplatin (CIS) is one of the most effective chemotherapeutics for ovarian cancer. Here, we investigated an experimental approach to increase CIS cytotoxicity and overcome cell resistance using nanoparticle-based combination treatments. Methods Polyethylenimine (PEI)-based magnetic iron oxide nanocomplexes were used for drug delivery in genetically matched CIS-resistant (A2780/CP) and -sensitive (A2780) ovarian cancer cells in the presence of a 20 mT static magnetic field. Magnetic nanoparticles (MNPs) were synthesized and bonded to PEI cationic polymers to form binary complexes (PM). The binding of CIS to the PM binary complexes resulted in the formation of ternary complexes PM/C (PEI–MNP/CIS) and PMC (PEI–MNP–CIS). Results CIS cytotoxicity increased at different concentrations of CIS and PEI in all binary and ternary delivery systems over time. Additionally, CIS induced cell cycle arrest in the S and G2/M phases and reactive oxygen species production in both cell lines. Ternary complexes were more effective than binary complexes at promoting apoptosis in the treated cells. Conclusion PEI-based magnetic nanocomplexes can be considered novel carriers for increasing CIS cytotoxicity and likely overcoming drug resistance of ovarian cancer cells.